2017
DOI: 10.3389/fnins.2017.00519
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Musicology Meets Embodied Cognition: Biocultural Coevolution and the Enactive Origins of Human Musicality

Abstract: Despite evolutionary musicology's interdisciplinary nature, and the diverse methods it employs, the field has nevertheless tended to divide into two main positions. Some argue that music should be understood as a naturally selected adaptation, while others claim that music is a product of culture with little or no relevance for the survival of the species. We review these arguments, suggesting that while interesting and well-reasoned positions have been offered on both sides of the debate, the nature-or-cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 192 publications
(240 reference statements)
0
29
0
Order By: Relevance
“…The novel and functional adaptations at the basis of the capacity to establish meaningful couplings with the world allow the living system to achieve a certain goal—ranging from the realization of a stable thermodynamic equilibrium with the environment in unicellular organisms to the participation in artistic events for more complex animals like us. For very basic forms of life, this ongoing bidirectional dependency may only relate to a quest for nutrition and the different adaptations this entails; but for more sophisticated beings, such as humans, needs and motivations span different situations and experiences and may include art and music ( van der Schyff and Schiavio, 2017 ; see also Dissanayake, 1988 , 1995 ; Kaufman, 2020 ). In both music-specific contexts and general bio-cognitive domains, it is suggested that the tension between operational closure and material openness is overcome when a veil of significance is casted upon the environment: this allows living systems to anticipate or address perturbations and take care of and restore their internal metabolic balance as well as their state of equilibrium with their ecology.…”
Section: The Ubiquity Of Skillful Adaptationmentioning
confidence: 99%
“…The novel and functional adaptations at the basis of the capacity to establish meaningful couplings with the world allow the living system to achieve a certain goal—ranging from the realization of a stable thermodynamic equilibrium with the environment in unicellular organisms to the participation in artistic events for more complex animals like us. For very basic forms of life, this ongoing bidirectional dependency may only relate to a quest for nutrition and the different adaptations this entails; but for more sophisticated beings, such as humans, needs and motivations span different situations and experiences and may include art and music ( van der Schyff and Schiavio, 2017 ; see also Dissanayake, 1988 , 1995 ; Kaufman, 2020 ). In both music-specific contexts and general bio-cognitive domains, it is suggested that the tension between operational closure and material openness is overcome when a veil of significance is casted upon the environment: this allows living systems to anticipate or address perturbations and take care of and restore their internal metabolic balance as well as their state of equilibrium with their ecology.…”
Section: The Ubiquity Of Skillful Adaptationmentioning
confidence: 99%
“…These scholars therefore increasingly draw from the resources offered by dynamical systems theory −a mathematical tool adopted to explore how complex systems develop in time through the convergence and divergence of its elements (Strogatz, 1994; Kelso, 1995). Work inspired by such insights trades the adoption of stimulus and response for sets of “differential equations that express the magnitude of variability between pairs of (non-linearly) coupled components” (van der Schyff et al, 2018), applying it to a vast range of domains, including music (Large et al, 2016; see also Schiavio et al, 2017a; van der Schyff and Schiavio, 2017a,b; Walton et al, 2014).…”
Section: Reconciling Dichotomiesmentioning
confidence: 99%
“…And at the other end, it can be seen as a promise of a new kind of humanity, transcending the limits set by our biological bodies and fallible human intelligence. From the perspectives of nondualistic 4E (embodied, embedded, enactive, and extended) cognition (e.g., Van der Schyff and Schiavio, 2017;Newen et al, 2018) and coevolution with technology (e.g., Ihde, 1990), we will see that the above-presented view rests on the somewhat misleading distinction between "natural humanity" and "unnatural technology." In terms of the evolutionary continuum, technology has been an integral part of the development of humanity for so long and in so fundamental a way that it is difficult to conceive of a world, and humanity, without technology.…”
Section: Introductionmentioning
confidence: 99%